AN ANALYSIS OF THE PREPARATION PROCESS OF MUNICIPAL EDUCATION PLAN OF RIO CLARO-SP. - da SIlva, Mariana Aparecida (2017)
The Municipal Education Plan (MEP) is an important instrument that serves as an action guide for the government as opposed to unpredictability. It should express the guidelines, goals and means by which the objectives will be achieved during its validity, such as the strategies and forms of collaboration of the federated entities, as well as the monitoring and constant evaluations of its implementation. This paper focuses on the analysis of the MEP of Rio Claro-SP. From a qualitative perspective, this work aims to follow the process of preparation of the MEP as an instrument of educational policy, through bibliographical and documentary analysis. It is based on the master's research entitled Municipal Education Plan of Rio Claro - SP: challenges and perspectives in guaranteeing the right to education. The academic production, more directly linked to the research object, and the works that can elucidate the socioeconomic and political context of the country, in its relations with the global context, served as support for the analysis of the documentary data. The first part of the paper reviews the conceptions of plans that have permeated the educational political history, evidencing the importance of public policy planning as a state policy. The second part sought to trace the construction of the MEP, from its outbreak, going through the first version of the document (prepared collectively and systematized by a Commission), until the second version (reviewed by the Municipal Council of Education of Rio Claro).